Utilizing Question-and-Answer Technique to Boost Students’ English-Speaking Skills - Lasim Muzammil; Andy Andy; Umi Tursini; Lesi Bebeto (Journey: Journal of English Language and Pedagogy, 2024)
A question-and-answer technique is one of the strategies to learn English-speaking skills. It invites the class to ask the concerned student questions and avoids a monologue where all the focus is on one person, which helps the teacher reduce tension. The purpose of this study was to confirm the impact of question-and-answer sessions on the speaking proficiency of first-grade senior high school students in Malang, Indonesia. A Quasi-experimental research design was employed since the present study utilized two intact groups. To find out the result, the researchers conducted a pre-test to measure the homogeneity of the group and a post-test to verify the technique's effectiveness. Based on the pre-test result, the groups were claimed to be homogenous before treatment was done since the significant value (.53) was greater than 0.05 (.53> 0.05). However, the post-test result after the treatment indicated that the two groups differed significantly at 0.05 levels as the sig. of the test results was less than 0.05 (.001<0.05). Furthermore, the descriptive statistics revealed better performance in the experimental than in the control group (76.56 > 66.22). It is summarized that the students who were taught using question-and-answer techniques had better speaking ability than those who were not. Therefore, the researchers recommended teachers apply this technique to their students to develop their speaking ability.